Archaeology of educational evaluation : epistemological spaces and political paradoxes - Grimaldi, Emiliano (London: Routledge, 2020)
"An Archaeology of Educational Evaluation: Epistemological Spaces and Political Paradoxes outlines the epistemology of the theories and models that are currently employed to evaluate educational systems, education policy, educational professionals and students learning. It discusses how those theories and models find their epistemological conditions of possibility in a specific set of conceptual transferences from mathematics and statistics, political economy, biology and the study of language. The book critically engages with the epistemic dimension of contemporary educational evaluation and is of theoretical and methodological interest. It uses Foucauldian archaeology as a problematizing method of inquiry within the wider framework of governmentality studies. It goes beyond a mere critique of the contemporary obsession for evaluation and attempts to replace it with the opening of a free space where the search for a mode of being, acting and thinking in education is not over-determined by the tyranny of improvement. This book will appeal to academics, researchers and post-graduate students in the fields of educational philosophy, education policy and social science"--
Includes bibliographical references and index.
Keywords: Educational evaluation; Knowledge, Theory of